Association of Clinicopathological Profile and Immunohistochemical Expression of KRAS and BRAF in Colorectal Carcinoma: A Cross-sectional Study - Mandira Mitra; Suman Ghosh; Niladri Sarkar; Anadi Roy Chowdhury (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Colorectal Carcinoma (CRC) is a multi-step process that occurs due to the accumulation of several genetic alterations. The most important alterations are related to the rat sarcoma viral oncogene homolog (RAS) and Rapidly Accelerated Fibrosarcoma (RAF), which have been implicated as key intermediates in the RAS-mediated signalling cascade. However, the levels of Kristen Rat Sarcoma Virus (KRAS) and v-raf Murine Sarcoma Viral Oncogene Homolog (BRAF) protein expression and their prognostic evaluation in CRC patients remain unknown. Aim: To investigate the immunohistochemical expression of KRAS and BRAF proteins in CRC. Materials and Methods: The present institutional-based cross-sectional observational study was conducted in a tertiary care centre in West Bengal, specifically in the Department of Pathology in collaboration with the Department of Surgery at Murshidabad Medical College and Hospital, Berhampore, West Bengal, India. A total of 26 CRC cases were enrolled in the present study, received over a period of one and a half years from January 2021 to June 2022. The parameters studied included demographic and clinical information of the patients, histopathological findings, pathological grade and stage of carcinoma, and immunohistochemical findings for KRAS and BRAF. For statistical analysis, data were entered into Microsoft (MS) Excel. Descriptive measures such as mean±Standard Deviation (SD), range, and percentage were used. The Chi-square test was used to determine the significance of the study. Results: A total of biopsy-proven CRC specimens were studied, consisting of 17 male patients (65.38%) with a male-to-female ratio of 1.9:1. The most common age group involved was 51-60 years (38%). Conventional adenocarcinoma accounted for the majority of cases (85%), with mucinous carcinoma comprising the remaining 15%. Among the 26 cases, 15 (58%) showed KRAS positivity, which was significantly associated with tumour grade and stage. Most of the cases were BRAF-negative. Out of the 21 cases where either KRAS or BRAF or both were positive, 20 cases showed high T stage (T3 and T4) and/or metastatic lesions (p-value 0.001). All four cases that were negative for both BRAF and KRAS belonged to the low T stage. Conclusion: A significant correlation was observed between the expression of KRAS and high-grade, high pathological Tumour, Node, Metastasis (TNM) T stage (T3 and T4) CRC. Therefore, KRAS Immunohistochemistry (IHC) biomarkers should be included in the standard diagnostic protocol for colorectal cancer, as they help identify KRAS-positive CRC cases that are resistant to targeted immunotherapy.